Design Strategies, Practical Considerations, and New Solution Processes of Sulfide Solid Electrolytes for All‐Solid‐State Batteries. Issue 18 (23rd April 2018) - Park, Kern Ho; Bai, Qiang; Kim, Dong Hyeon; Oh, Dae Yang; Zhu, Yizhou; Mo, Yifei; Jung, Yoon Seok
Abstract: Owing to the ever‐increasing safety concerns about conventional lithium‐ion batteries, whose applications have expanded to include electric vehicles and grid‐scale energy storage, batteries with solidified electrolytes that utilize nonflammable inorganic materials are attracting considerable attention. In particular, owing to their superionic conductivities (as high as ≈10 −2 S cm −1 ) and deformability, sulfide materials as the solid electrolytes (SEs) are considered the enabling material for high‐energy bulk‐type all‐solid‐state batteries. Herein the authors provide a brief review on recent progress in sulfide Li‐ and Na‐ion SEs for all‐solid‐state batteries. After the basic principles in designing SEs are considered, the experimental exploration of multicomponent systems and ab initio calculations that accelerate the search for stronger candidates are discussed. Next, other issues and challenges that are critical for practical applications, such as instability in air, electrochemical stability, and compatibility with active materials, are discussed. Then, an emerging progress in liquid‐phase synthesis and solution process of SEs and its relevant prospects in ensuring intimate ionic contacts and fabricating sheet‐type electrodes is highlighted. Finally, an outlook on the future research directions for all‐solid‐state batteries employing sulfide superionic conductors is provided. Abstract : Sulfide Li + and Na + superionic conductors are considered to be enabling materials in safe and high‐energy all‐solid‐state batteries. This progress report provides a brief review on superionic conductor solid electrolytes through both experimental and theoretical approaches on ionic conductivity, electrochemical stability, interface compatibility, and air‐stability. Further, design strategies, practical considerations, and emerging solution processes of solid electrolytes are discussed.